FERMENTASI TEPUNG SORGUM MERAH OLEH Lactobacillus plantarum ATCC 14977 UNTUK MENDUKUNG DIVERSIFIKASI PANGAN LOKAL - silvy novita putri; Sudiyono Sudiyono; Yuni Agung Nugroho; Dea Shania Purnomo (BUANA SAINS, 2025)
Red sorghum (Sorghum bicolor L.) is a promising local food resource in Indonesia, but its utilization is hindered by its inherent bitterness, primarily caused by tannins. This study aimed to reduce bitterness and improve functional properties through fermentation using Lactobacillus plantarum. A Randomized Block Design with two factors—inoculum concentration (3 levels) and fermentation time (3 levels)—was applied, resulting in nine treatments. The tannin content, protein digestibility, solubility, swelling power, and water absorption capacity were analyzed. Fermentation significantly reduced tannin content by up to 60% (p 0.005) and increased protein digestibility from 45% to 70%. Simultaneously, solubility, swelling power, and water absorption capacity improved from 33.45% to 55.87%, 7.28 g/g to 9.05 g/g, and 11.92% to 13.68%, respectively. Optimal results were obtained after 48 hours of fermentation. These findings demonstrate that L. plantarum fermentation effectively mitigates bitterness while enhancing nutritional and functional qualities, offering a viable processing method to promote red sorghum as a functional food ingredient and support food diversification strategies in Indonesia. Further research should focus on sensory evaluation and application in food product development.